Effect of Bioturbation on Reservoir Rock Quality of Reservoir Sandstones in the Baram Delta, Offshore Sarawak, Malaysia - Ben-Awuah, Joel; Padmanabhan, E. (Shiyou Kantan Yu Kaifa, 2015)
With the Baram Delta in Malaysia as research subject, the effect of bioturbation on porosity and permeability of reservoir sandstones is evaluated and analyzed based on core and thin section analysis, EDX (energy-dispersive X-ray), FESEM (Field Emission Scanning Electron Microscope), mercury porosimetry and spot permeametry measurement. Samples are from cored intervals of two wells in the Baram Delta, W-1 and W-6. Analysis results indicate that the cored intervals in well W-1 are dominated by Diplocraterion ichnofabrics, intensely bioturbated, sediment packing activity is observed, and fine grade materials (clays and organic matter) from the host sediment are incorporated into burrow fills and linings, thereby decreasing isotropy and sorting of the sediments and reducing the local porosity and permeability in the burrows. The cored intervals in well W-6 are dominated by Ophiomorpha ichnofabrics, highly to intensely bioturbated, sediment cleaning activity by burrowing organisms results in cleaner and well sorted burrow fill materials, and clays and mud are cleaned from the burrow fill and host sediment and concentrated in the burrow linings. Porosity and permeability of reservoir rocks in the Baram Delta have therefore either been enhanced or reduced by bioturbation depending on the type of burrow, fill material and burrowing activity.